Clinical Investigation:Relationships Between Illness Perceptions, Coping and Psychological Morbidity in Kidney Transplants Patients. (March 2016) - Knowles, Simon R.; Castle, David J.; Biscan, Shellie M.; Salzberg, Michael; O'Flaherty, Emmett B.; Langham, Robyn
ABSTRACT : Background: : The aim of this study was to explore the effect of kidney transplantation (KT) on psychological distress and quality of life (QoL) in patients with end‐stage kidney disease using the Common Sense Model of illness adjustment. Materials and Methods: : A total of 52 individuals (35 men and 17 women) with an average age of 53.54 years from a large metropolitan nephrology outpatient clinic participated. Results: : Poorer health status, illness perceptions and increased engagement in maladaptive coping were associated with psychological distress (specifically anxiety and depression) and poorer QoL. Hierarchical regression, after correcting for KT characteristics (years since most recent KT, number of transplants) indicated that poorer illness status and illness perception predicted QoL. After controlling for KT characteristics, poorer illness status and greater engagement in maladaptive coping predicted depression. In contrast, poorer illness perceptions and greater engagement in maladaptive coping predicted anxiety. Adaptive problem‐focused and emotion‐focused coping styles were not found to predict anxiety, depression or QoL. Conclusions: : The finding of the present study emphasize on the importance of exploring and understanding the effect of illness status, illness perceptions and coping patterns in patients who have underwent KT.